Bridging the Gap from Classroom-based Learning to Experiential Professional Learning: A Hong Kong Case - Du-Babcock, Bertha (Dinamika Ilmu: Jurnal Pendidikan, 2016)
This paper describes and evaluates a funded longitudinal teaching development project that aims to bridge the gap from classroom-based theory learning to experiential professional learning, and thereby prepare ideal and competent world class graduates. To align with the University's shared mission to foster links with the business community, the design of the internship program has a threefold purpose and was implemented in stages. It intends to enhance students' professional awareness-knowledge-skills through a multi-leveled approach integrating classroom learning with professional practice. A debriefing mechanism was also built in enabling students to share their learning and professional challenges, and theory application to problem-solving scenarios. A 360 degree multiple evaluation procedure were used to measure the project effectiveness, including the use of industry consultants, student interns, hosts, and academic supervisors.   The project has proved to promote closer ties with the business community and enhance students' professional competencies to increase future success in the competitive job market. The impact of the internship program is significant in two aspects.  From the perspective of student learning, the internship allows students to understand how they can improve business efficiency by applying communications theories.  From the teaching perspective, the successful and unsuccessful intern experiences can be drawn upon in developing class-room teaching. These lessons can focus on preparing students to solve real-world business communication problems.